Multi-product production routing problem by consideration of outsourcing and carbon emissions: particle swarm optimization. Issue 8 (3rd August 2021) - Salehi Sarbijan, M.; Behnamian, J.
Abstract : Studies have shown that the production and routing problems have an impact on each other, and the integration of these decisions can considerably improve decision making and reduce costs. In this regard, this research studies the effect of outsourcing on a multi-product production routing problem considering environmental impact. In addition to minimizing greenhouse gas emission costs, in this study, the objective function of the problem includes production, maintenance and outsourcing costs. After modelling the problem as mixed-integer linear programming, because of its NP hardness, a particle swarm optimization (PSO) algorithm is also proposed for solving the problem, especially in large-size instances. To verify the effectiveness of the proposed algorithm, a set of random test problems with different structures is generated. Finally, the PSO and variable neighbourhood search (VNS) algorithms are compared, and the results show that the PSO is better than the VNS algorithm.